2013
DOI: 10.1007/s11832-013-0505-8
|View full text |Cite
|
Sign up to set email alerts
|

Flexed-knee gait in children with cerebral palsy: A 10-year follow-up study

Abstract: Background While several studies have evaluated the short-term effectiveness of conservative and surgical treatment of flexed-knee gait in children with cerebral palsy (CP), few have explored the long-term outcomes using gait analysis. The purpose of this study was to examine, through gait analysis, the 10-year outcomes of flexed-knee gait in children with CP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 30 publications
0
8
0
2
Order By: Relevance
“…In our study, DHL, as part of a SEMLS, was effective for the treatment of flexed knee gait and the parameters of 3D gait analysis after surgery were similar to those in previous studies (Table 5 ). Many authors have reported short-term favorable outcomes in terms of sagittal knee joint parameters after DHL [ 2 , 4 8 , 17 ], and recent studies investigating the long-term outcomes of DHL showed that these improvements were maintained at over 10 years postoperatively [ 11 , 13 , 14 , 18 ]. The present study also found that the improvement in knee flexion at initial contact, minimum knee flexion in the stance phase, and knee ROM after DHL was maintained during the follow-up duration in patients with GMFCS level I and II, although there was concern that the favorable surgical outcomes might diminished over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, DHL, as part of a SEMLS, was effective for the treatment of flexed knee gait and the parameters of 3D gait analysis after surgery were similar to those in previous studies (Table 5 ). Many authors have reported short-term favorable outcomes in terms of sagittal knee joint parameters after DHL [ 2 , 4 8 , 17 ], and recent studies investigating the long-term outcomes of DHL showed that these improvements were maintained at over 10 years postoperatively [ 11 , 13 , 14 , 18 ]. The present study also found that the improvement in knee flexion at initial contact, minimum knee flexion in the stance phase, and knee ROM after DHL was maintained during the follow-up duration in patients with GMFCS level I and II, although there was concern that the favorable surgical outcomes might diminished over time.…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been concerns that DHL might aggravate anterior pelvic tilt, lumbar hyperlordosis, and genu recurvatum, and eventually induce crouch gait [ 2 , 17 ]. Even though the length of time of improvement in knee motion are maintained is unclear, several studies showed that the improvements after DHL were maintained 10 years postoperatively in patients with CP [ 11 , 13 , 14 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the treatment plan that is implemented, motion analysis can assess the outcome of the interventions (Table ) . Postoperative motion analysis is usually conducted one year after the surgery.…”
Section: Interdisciplinary Treatment Planningmentioning
confidence: 99%
“…Other authors defined KFGP by a knee flexion at initial contact superior to15° [5] or 17° [6] corresponding to one standard deviation (SD) above the mean flexion at initial contact for a typically developing children.…”
Section: Introductionmentioning
confidence: 99%